PROFIL MISKONSEPSI SISWA PADA MATERI PECAHAN BERDASARKAN TINGKAT KEMAMPUAN MATEMATIKA SISWA - Nurhamdiah Nurhamdiah; Ahmad Nizar Rangkuti (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2019)
Elementary school sixth-grade students still experience misconceptions fractions causing low student mathematics learning outcomes. The purpose of this study is to find out the student's misconceptions in the fraction material. The type of research conducted is descriptive qualitative research. The subjects studied were 6 grade VI elementary school students, 2 subjects with high mathematical ability levels, 2 subjects with moderate mathematical ability levels, and 2 subjects with low mathematical ability levels. Data collection methods used were interviews and multiple-choice tests based on fraction material. The results of the study stated: (1) The students' dominant misconceptions in the concept of calculating fraction distribution operations. (2) Misconceptions experienced by students with high mathematical abilities are less than students with moderate and low mathematical abilities. With this research, the teacher can find out the students' misconceptions in the subject matter fractions and the teacher can be more maximal in teaching the concept of fractions. Keywords: Misconception, Fraction Material, Mathematical Ability